2016
DOI: 10.1136/bmjopen-2016-011230
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, observational study comparing automated and visual point-of-care urinalysis in general practice

Abstract: ObjectivePoint-of-care testing (POCT) urinalysis might reduce errors in (subjective) reading, registration and communication of test results, and might also improve diagnostic outcome and optimise patient management. Evidence is lacking. In the present study, we have studied the analytical performance of automated urinalysis and visual urinalysis compared with a reference standard in routine general practice.SettingThe study was performed in six general practitioner (GP) group practices in the Netherlands. Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…In human clinical practice, it has been shown that when compared with visual reading, automated POC analysis of urine dipsticks may be associated with higher sensitivity, higher reproducibility and higher agreement with a laboratory reference method, being also userfriendly. [18][19][20] Consequently, the automated method is currently recommended 21 and several human medical institutions routinely employ it. 22 23 However, these human medical studies were limited in scope (one parameter investigated), 18 number and experience of subjects, 19 20 as well as utilising diferent strips for visual and automated methods.…”
Section: Introductionmentioning
confidence: 99%
“…In human clinical practice, it has been shown that when compared with visual reading, automated POC analysis of urine dipsticks may be associated with higher sensitivity, higher reproducibility and higher agreement with a laboratory reference method, being also userfriendly. [18][19][20] Consequently, the automated method is currently recommended 21 and several human medical institutions routinely employ it. 22 23 However, these human medical studies were limited in scope (one parameter investigated), 18 number and experience of subjects, 19 20 as well as utilising diferent strips for visual and automated methods.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the visual read-out and the CLINITEK device had very good agreement for the measurement of haematuria (κ = 0.83) as well as for nitrites (κ = 0.88), a biomarker for urinary tract infections [27]. It also had good agreement for leukocytes, which somewhat reflects a previous finding in routine hospital tests, where agreement between visual and automated read-outs (using another analyser) was very good for nitrites and good for haematuria albeit poor for leukocytes [17]. The agreement was, however, only fair to moderate for all other biomarkers.…”
Section: Discussionmentioning
confidence: 53%
“…Point-of-care testing requiring little equipment and minimal training can improve healthcare globally, in particular in settings where high quality medical care is a challenge [22]. Many studies have compared performance of visual read-out vs automated read outs (using CLINITEK or other devices), where they tended to demonstrate on-par or superior performance of the analyser as compared to visual read-out [17, 23]. However, they were largely evaluated in controlled laboratory or hospital settings [24, 25], and usually focused on a single parameter to about three parameters [15, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cobas u411 Analyzer (Roche Diagnostics) is an automated, reflectance photometry‐based dipstick urinalysis instrument designed for use with Roche's CHEMSTRIP 10UA technology. The advantages of automated urinalysis established in human medicine include decreased operator time, decreased turn‐around time (if the automated results are connected to the laboratory information management system or LIMS), increased precision (decreased intra‐ and interobserver error), elimination of transcription error to the LIMS, and the potential for improved accuracy . Increased accuracy is particularly important for some analytes, such as pH, which are known to suffer from poor diagnostic accuracy using dipstick urinalysis techniques …”
Section: Introductionmentioning
confidence: 99%